(untitled) (Foro de Educacion, 2026)
The project titled Development of a Center of Excellence for Services to Stimulate Child Development and Learning Behavior at the La-orutis Demonstration School, Suan Dusit University, Lampang Center aimed to establish a Center of Excellence for screening, diagnosis, service planning, and intervention to promote child development and learning behavior within the school. The center was developed using a Participatory Action Research (PAR) approach, engaging multidisciplinary experts, parents, educational personnel, and the institution. The core component of the service model was the Individualized Service Plan, designed specifically for children with special needs and grounded in the recognition of each child’s unique developmental differences. The approach integrated specialized services into early childhood and primary education while fostering inclusive education, enabling students with special needs to learn alongside their peers in mainstream classrooms. The successful establishment of the La-or Learning and Development Center (LDC) at the La-orutis Demonstration School, Lampang, yielded highly positive outcomes. The results indicated that 93.6% of students showed improved learning development. This success resulted from the center’s effective interdisciplinary collaboration—incorporating specialized physicians, therapists, teachers, and parents—to provide holistic and individualized care for students experiencing developmental, psycho-emotional, and behavioral challenges. Effective childrearing in Thai medical centers of excellence requires strengthened caregiver training for single-parent contexts, careful management of technology use to reduce risks of pseudo-autism and language delay, and balanced parenting approaches to support children’s independence.